2018
DOI: 10.1002/acm2.12259
|View full text |Cite
|
Sign up to set email alerts
|

Survey of 5 mm small‐field output factor measurements in Australia

Abstract: The Australian Radiation Protection and Nuclear Safety Agency (ARPANSA) held a comparison exercise in April 2016 where participants came to ARPANSA and measured the output factor of a nominal 5 mm cone attached to the ARPANSA Elekta Synergy (Elekta, Crawley, UK) linear accelerator. The goal of the exercise was to compare the consistency and methods used by independent medical physicists in measuring small‐field output factors. ARPANSA provided a three‐dimensional scanning tank for detector setup and positionin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…The output factors measured here are compared to the Cheng et al (2016) reported output factors in table 5, which shows reasonable agreement. The largest difference is about 3% at the smallest cones, which is within the institutional variation of 3.6% seen by Oliver et al (2018). This difference is also expected as measurements at these small field sizes suffer from relatively high uncertainties in both setup accuracy and correction factors while Monte Carlo is generally accepted to be independent of small field issues.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The output factors measured here are compared to the Cheng et al (2016) reported output factors in table 5, which shows reasonable agreement. The largest difference is about 3% at the smallest cones, which is within the institutional variation of 3.6% seen by Oliver et al (2018). This difference is also expected as measurements at these small field sizes suffer from relatively high uncertainties in both setup accuracy and correction factors while Monte Carlo is generally accepted to be independent of small field issues.…”
Section: Discussionsupporting
confidence: 59%
“…If we specifically look at output factors, large variation exists across institutions using the same types of accelerators and equipment. The paper by Oliver et al (2018) showed that, even for measurements on the same accelerator, output factors between physicists from different institutions show a relatively large variation. While a large body of work exists on identifying the challenges in small fields, it is still difficult to implement these ideas in the clinic.…”
Section: Introductionmentioning
confidence: 99%
“…A detector‐reading ratio range of 7.8% is found in Oliver et al 2017 for 5 mm cones measured in Elekta Synergy using IBA SFD, Razor, EFD, and PTW T60017 and T60019 (microDiamond). This range decreased to 6.1% by applying appropriate output correction factors.…”
Section: Resultsmentioning
confidence: 84%
“…The measurements involved several different detector types, correction factors, setup variations, and analysis methods, highlighting the importance of completing accurate measurements with suitable detectors as well as obtaining or deriving appropriate correction factors [5].…”
Section: Resultsmentioning
confidence: 99%